2001
DOI: 10.1017/s1049096501000373
|View full text |Cite
|
Sign up to set email alerts
|

American Women and Politics in the Media: A Review Essay

Abstract: The study of women and politics in the media is a relatively young subfield, blessed with scholarship from the fields of communications, cultural studies, history, sociology and political science. Members of these fields use methodologies—such as semiotics, qualitative analysis, and quantitative content analysis—to examine the content of communication about women and politics in news and advertising. Studies of the impact of messages use polls, experiments, and focus groups. Scholars draw primarily upon theori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…This raises the question whether female politicians tend to be more skeptical towards becoming a source of news, or whether the media treat female politicians differently than male politicians. Not only are women often under-represented in the news, international research has also shown that female politicians are often treated differently by the media than their male colleagues Everitt, 2000, 2003;Kahn, 1992Kahn, , 1993Kahn, , 1994aKahn, , 1994bKahn, , 1996Larson, 2001). For example, female politicians are often primed to take up 'softer' issues, such as welfare and policies related to children and family.…”
Section: The Relationship Between the Media And Female Politiciansmentioning
confidence: 99%
“…This raises the question whether female politicians tend to be more skeptical towards becoming a source of news, or whether the media treat female politicians differently than male politicians. Not only are women often under-represented in the news, international research has also shown that female politicians are often treated differently by the media than their male colleagues Everitt, 2000, 2003;Kahn, 1992Kahn, , 1993Kahn, , 1994aKahn, , 1994bKahn, , 1996Larson, 2001). For example, female politicians are often primed to take up 'softer' issues, such as welfare and policies related to children and family.…”
Section: The Relationship Between the Media And Female Politiciansmentioning
confidence: 99%
“…The influence of athletics enters a number of discourses including education (e.g., school administrations' oversight of compliance with Title IX), consumer behavior (e.g., consumers' purchases of recreational and athletic equipment), and politics (e.g., during the 1996 and 2000 US Presidential campaigns, massive political strategies were aimed at winning the vote of the soccer mom, Carroll 1999; Glowka and Lester 1997;Larson 2001). Athletics at all levels remain increasingly popular, even as corruption scandals disillusion fans and institutions of higher education are held accountable for (often egregious) recruiting violations (Thelin and Wiseman 1989).…”
Section: Introductionmentioning
confidence: 99%
“…This impression led to an increased call for more female leadership during the health crisis (Katz, 2021; PAHO, 2021; UN Women, 2020). Past research illustrated that media reports are often biased when depicting female and male politicians (Larson, 2001), often endorsing traditional gender stereotypes (see also Atkeson & Krebs, 2008; Kittilson & Fridkin, 2008; Hayek & Russmann, 2020).…”
Section: Discussionmentioning
confidence: 99%